2009
DOI: 10.1111/j.1540-8159.2008.02197.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Dedicated Versus Integrated Bipolar Defibrillator Leads with CRT‐Defibrillators: Results from a Prospective Multicenter Study

Abstract: Introduction: Right ventricular (RV) anodal stimulation may occur in cardiac resynchronization therapy defibrillators (CRT-D) when left ventricular (LV) (PACE 2009; 32:157-165) integrated, dedicated, anodal stimulation, undersensing, oversensing, inappropriate therapies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The type of ICD lead (dedicated or integrated bipolar) did not influence NAO and this observation should help clarify ongoing discussion regarding the difference in sensing between shocking lead types 18,19 . While the incidence of T‐wave oversensing, atrial oversensing on the ventricular lead, and muscle oversensing was very low, these episodes may be expected to be more common in integrated bipolar leads compared to dedicated bipolar leads.…”
Section: Discussionmentioning
confidence: 78%
“…The type of ICD lead (dedicated or integrated bipolar) did not influence NAO and this observation should help clarify ongoing discussion regarding the difference in sensing between shocking lead types 18,19 . While the incidence of T‐wave oversensing, atrial oversensing on the ventricular lead, and muscle oversensing was very low, these episodes may be expected to be more common in integrated bipolar leads compared to dedicated bipolar leads.…”
Section: Discussionmentioning
confidence: 78%
“…Anodal stimulation has been also described in patients receiving a CRT system, especially in those involving RV defibrillation lead with a true bipolar design for the pace/sense function . Integrated bipolar RV defibrillator leads (those that utilize the distal shocking coil as the proximal pacing electrode) showed a significantly lower incidence of RV anodal stimulation when compared to dedicated bipolar RV defibrillation leads . Today true bipolar LV leads (allow the option of programming bipolar pacing between two electrodes of the same LV lead) allow avoidance of this phenomenon excluding the RV lead from the LV pacing configuration.…”
Section: Discussionmentioning
confidence: 99%
“…7 Integrated bipolar RV defibrillator leads (those that utilize the distal shocking coil as the proximal pacing electrode) showed a significantly lower incidence of RV anodal stimulation when compared to dedicated bipolar RV defibrillation leads. 8 Today true bipolar LV leads (allow the option of programming bipolar pacing between two electrodes of the same LV lead) allow avoidance of this phenomenon excluding the RV lead from the LV pacing configuration. New quadripolar LV leads allow different true bipolar pacing configurations for better stimulation threshold or avoidance of phrenic stimulation.…”
Section: Pace Vol 38mentioning
confidence: 99%
“…In a direct comparison of the 2 leads, Degeratu et al reported that there were more inappropriate arrhythmia detection (because of lead failure) with dedicated bipolar leads than with integrated bipolar leads (17.8% versus 4.3%). 16 Nevertheless, Freedman et al 17 in a study with 292 patients who were randomly assigned to receive dedicated or integrated bipolar RV leads at the time of cardiac resynchronization therapy-defibrillator implantation reported that integrated bipolar RV defibrillator leads had a significantly lower incidence of RV anodal stimulation when compared with dedicated bipolar RV defibrillation leads, but with no clinically detectable oversensing or undersensing, and with no inappropriate ventricular tachyarrhythmia detections for either lead type. Whether sensing configuration has any relevance in patients with BrS has not been specifically evaluated.…”
Section: Discussionmentioning
confidence: 99%